UPAYA PENINGKATAN PEMBELAJARAN SEPAKBOLA MENGGUNAKAN PERMAINAN SEPAKBOLA MINI PADA SISWA KELAS X SMK TI TAMAN SISWA LUBUK PAKAM TAHUN AJARAN 2018/2019 - Ryan Deseca (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
This study aims to improve soccer learning using mini soccer games in class X SMK TI Taman Siswa Lubuk Pakam T.A. 2018/2019. The use of this research method is classroom action research (CAR). The subjects of this research were 28 students of class X SMK TI Taman Siswa Lubuk Pakam. The increase in student learning outcomes in learning football using mini football games in class X SMK TI Taman Siswa Academic Year 2018/2019 cannot be separated from the good learning strategies used by teachers, where using mini soccer games makes soccer learning activities according to students' physical characteristics, where the equipment used is in accordance with the physical abilities and body size of students and the rules used are adapted to the learning needs of students to make the learning outcomes achieved by students optimally.